Interaction design for security based on social context. Issue 154 (October 2021) - Zhang, Jiaxin; Luximon, Yan
Abstract: Social context is a vital component of Human-Computer Interaction (HCI) design for security; however, there is little discussion about how to provide security functions based on the social context. This study examines the fit between security design and social contexts in mobile payment applications by investigating preferences and perceptions of security design based on the task-technology fit model and the technology acceptance model. To approach the fit of security design in different social contexts, this study followed the approach proposed by design science research and employed a full factorial design experiment. We developed two interfaces—a customizable interface without feedback information and a customizable interface with feedback information—and asked participants to modify security settings in the interfaces according to social contexts, conduct payment transactions, and report their perceptions of security and usability in four payment scenarios. The observed behaviors in relation to security settings and perceptions revealed the fit for security settings and feedback design in different social contexts. Implications were provided to allow insights for security design in mobile payment transactions according to social contexts. Highlights: Users have various preferences for security design according to social contexts in mobile payment transactions. The fit between security design and social contexts was investigated based on the task-technology fit model and the technology acceptance model. Social presence and trust are two contextual factors which influence the fit. Based on the perception of security and usability, designers can embed fewer security settings in the high trust context, and provide users with brief feedback information in the high social presence context.